Zincophilic CuO as electron sponge to facilitate dendrite-free zinc-based flow battery - Jin Seong Cha; Sanghyeon Park; Noh-Uk Seo; Yun-Chan Kang; Chan-Woo Lee; Jung Hoon Yang (Nature Communications)
Abstract Zinc (Zn)-based batteries have been persistently challenged by the critical issue of inhomogeneous zinc deposition/stripping process on substrate surface. Herein, we reveal that zinc electrodeposition behaviors dramatically improved through the introduction of highly zincophilic copper oxide nanoparticles (CuO NPs). Strong electronic redistribution between Zn and CuO explains the high Zn affinity on CuO, with negligible nucleation overpotential. Additionally, CuO exhibits remarkable electron-accepting and -donating capabilities in electron-rich and electron-deficient environments, resembling a sponge. This ‘Electron Sponge’ effect emerges from stable Zn-O bonding in CuO, enhancing electron duality in the Zn-O bond region. This unique strategy is pivotal in mitigating dendritic growth, fostering dendrite-free zinc-based flow batteries with enhanced rate performance and cyclability. It presents significant performance with not only high energy density (180 Wh L−1) but also the long cycle stability (> 2500 cycles) at high current density (140 mA cm−2).